KERAPATAN DAN PENUTUPAN LAMUN PADA DAERAH TANGGUL PEMECAH OMBAK DI PERAIRAN DESA TEREBINO PROPINSI SULAWESI TENGAH - Ira, Ira; Oetama, Dedi; Juliati, Juliati (Aqusains: Jurnal Ilmu Perikanan dan Sumberdaya Perairan, 2013)
Waters Terebino village has a fairly extensive seagrass. However, since the breakwater, seagrass density and percent cover is changes. This study aims to look at the seagrass density and percent cover on a breakwater area. Results are expected to provide useful information and relevant parties in an effort to manage a sustainable marine biological resources and as a comparison for future research. Determination of the presence of seagrass station based around a breakwater and compare with seagrass which there is no breakwater. Research methods using transect quadrant 50 x 50 cm. The results showed that in the area of seagrass that no breakwater dike has a density and percent cover two times higher than the seagrass area contained a breakwater.